A banking system in transition: the origin, concept and growth of the Indonesian banking system - Charlesworth, Harold Karr (Djakarta, New Nusantara Pub. Co., 1959)
This book shows that Indonesian public need to know the developments which have occurred in the field of banking so that they can gain an accurate knowledge of their activities.
Includes bibliographical references
mf 22/01/2019
Loans
Keywords: Banks and banking; Indonesia